2000
DOI: 10.1097/00004714-200002000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine-Nefazodone Interaction in Healthy Subjects

Abstract: The pharmacokinetic interaction between nefazodone and carbamazepine was investigated in 12 healthy male volunteers. Subjects received nefazodone 200 mg twice daily for 5 days, and blood sample collection was performed on day 5 for 0- to 48-hour pharmacokinetic analysis. A 4-day wash-out phase then followed from days 6 to 9. Carbamazepine 200 mg was administered once daily from days 10 to 12, and then 200 mg was given twice daily from days 13 to 44. A 0- to 48-hour pharmacokinetic analysis was performed on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 24 publications
0
5
2
Order By: Relevance
“…This contrasts with other studies where a comedication with carbamazepine led to a decrease of plasma concentrations of drugs that are CYP3A4 substrates, such as citalopram (Leinonen et al, 1996;Steinacher et al, 2002), mianserin (Eap et al, 1999), nefazodone (Laroudie et al, 2000), sertraline (Khan et al, 2000) and tricyclic antidepressants (Leinonen et al, 1991). The present 'negative' result may be explained by the major pathway of venlafaxine being controlled by CYP2D6, with N-demethylation, which occurs both by CYP2C19 and by CYP3A4, being a minor pathway (Fogelman et al, 1999).…”
Section: Discussioncontrasting
confidence: 95%
“…This contrasts with other studies where a comedication with carbamazepine led to a decrease of plasma concentrations of drugs that are CYP3A4 substrates, such as citalopram (Leinonen et al, 1996;Steinacher et al, 2002), mianserin (Eap et al, 1999), nefazodone (Laroudie et al, 2000), sertraline (Khan et al, 2000) and tricyclic antidepressants (Leinonen et al, 1991). The present 'negative' result may be explained by the major pathway of venlafaxine being controlled by CYP2D6, with N-demethylation, which occurs both by CYP2C19 and by CYP3A4, being a minor pathway (Fogelman et al, 1999).…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, the expression of CYP3A4 can be induced [53] and therefore there is the potential for a number of inducer drugs, herbal supplements and pesticides to increase the clearance with corresponding lower Css levels of these derivatives. This is supported by the observation that in healthy subjects coadministration of carbamazepine (100 to 400 mg/day, depending on the study) substantially reduced exposure to nefazodone and trazodone and their main metabolites (44-94% and 60-76%, respectively) [54][55], again with less effect on ziprasidone AUC (35%) possibly because CYP3A4 mediates only one-third of its biotransformation [22]. Likewise, rifampicin 600 mg/day reduced the mean exposure to buspirone by about 90%, increasing the PmP-to-buspirone ratio about eight-fold in healthy subjects [19].…”
Section: Cyp-mediated N-dealkylation Of Arylpipera-zine Derivativesmentioning
confidence: 73%
“…However, the elimination of lorazepam, a benzodiazepine agent not primarily metabolized by oxidative processes in the liver, was not affected by coadministration of nefazodone [154]. In a recent study concomitant administration of nefazodone with carbamazepine, both substrate and inducer of CYP3A4, resulted in a small increase in plasma carbamazepine levels and a marked decrease in plasma concentrations of nefazodone and its major metabolites [155]. Another in vivo study has shown a modest 35% increase in plasma concentrations of haloperidol, whose metabolism involves CYP3A4 and CYP2D6, when coadministered with nefazodone [156].…”
Section: Nefazodonementioning
confidence: 99%